Mandatory Financial Stability Assessments Under the Financial Sector Assessment Program : Update. (Policy Papers; Policy Paper, 2013)
In September 2010, the Executive Board made financial stability assessments under the Financial Sector Assessment program (FSAP) a regular and mandatory part of bilateral surveillance under Article IV for jurisdictions with systemically important financial sectors. This decision recognized that although financial sector issues were at the core of the Fund's surveillance mandate, the FSAP as designed in the late 1990s had severe limitations as a tool. Voluntary participation, the low frequency of assessments, and their very broad coverage (particularly in emerging market and developing countries, where assessments are typically conducted jointly with the World Bank) limited the usefulness of the FSAP for surveillance. Building on the revamp of the FSAP during the 2009 program review that delineated the institutional responsibilities of the Fund and the World Bank and defined the content of the stability assessment under the FSAP, the Executive Board took the next step in 2010 to make these stability assessments mandatory every five years for members with systemically important financial sectors.